Lung Cancer - Modern Multidisciplinary Management 2021
DOI: 10.5772/intechopen.95494
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Oncotherapy through Novel Modalities: Gas Plasma and Nanoparticle Technologies

Abstract: Cold atmospheric pressure plasma (CAP) is emerging as new healthcare technology and it has a high potential through physical and chemical effects for cancer treatment. Recently, CAP, plasma activated liquid (PAL), and nanomaterial have been significant advances in oncotherapy. Reactive oxygen-nitrogen species (RONS), electrical field, and other agents generated by CAP interact with cells and induce selective responses between the malignant and normal cells. Nanomedicine enhances therapeutic effectiveness and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…CAP helps reduce the resistance of cancer cells to chemotherapy drugs, [ 56,57 ] for example, TRAIL‐resistant colorectal cancer cells. [ 58 ] Here, we examined one of the most important resistance mechanics. We found that all of the combination treatments with PAM restore CAR sensitivity in resistant A2780 CP and SKOV‐3 OC cells.…”
Section: Discussionmentioning
confidence: 99%
“…CAP helps reduce the resistance of cancer cells to chemotherapy drugs, [ 56,57 ] for example, TRAIL‐resistant colorectal cancer cells. [ 58 ] Here, we examined one of the most important resistance mechanics. We found that all of the combination treatments with PAM restore CAR sensitivity in resistant A2780 CP and SKOV‐3 OC cells.…”
Section: Discussionmentioning
confidence: 99%